John Rawls : eine theorie der gerechtigkeit - Höffe, Otfried (Klassiker auslegen, 2013)
A Theory of Justice is the most important 20th century English-language work on political ethics. John Rawls develops a persuasive theory about the interface between ethics and political philosophy and, in addition, he succeeds in initiating a series of fundamental paradigm shifts.